Femicide trends at the start of the 21st. century: Prevalence, risk factors and national public health actions - Richard Whittington; Alina Haines-Delmont; Johan Hå‌kon Bjø‌rngaard (Global Public Health, 2023)
Lethal violence requires a gender-based analysis which recognises that femicide is different from homicide in many ways. Structural factors such as national income and wealth equality together with government policies may influence the scale of the problem globally. This study is an original attempt to examine associations between femicide rates, these structural factors and national action plans using a longitudinal design. Data from two international surveys were combined to examine anti-femicide actions (n = 133 countries) and temporal femicide prevalence trends (n = 66 countries) in the context of national income and wealth inequality factors. The United Nations Survey of Crime Trends and Operations of Criminal Justice Systems was used to estimate femicide rates per country 2003–2014 and the World Health Organisation Global Status Report on Violence Prevention provided data on policy initiatives in place by 2014. Results indicate that femicide rates decreased by 32% worldwide but increased by 26% in low- and medium-income countries. The structural factors of low income and high inequality were significantly negatively associated with the 2014 femicide rate. Structural factors must be addressed alongside policy and legal initiatives if significant gains are to be made toward eradicating violence against women and girls.